Fully integrated voiceband codec in a standard digital CMOS technology. - Pernici, S. (IEEE Journal of solid state circuits)
A 2.7-V complete voiceband codec with high-performance speech interfaces is presented. It includes a low-noise microphone preamplifier and loudspeaker/earpiece drivers. In the 4-kHz signal bandwidth, the ADC achieves a dynamic range of 80 dB and a full scale S/(THD + N) ratio of 71 dB, while the DAC performs 84 dB and 75 dB, respectively. These performances have been obtained in a pure digital low-cost CMOS process. The only components used are standard nMOS and pMOS transistors, parasitic vertical PNP bipolar transistors, unsalicided poly resistors, nonlinear poly-nwell capacitors, and a few small linear capacitors made with a sandwich of five metals and poly. The active area is 2.7 mm2 in a 0.35-μm, five metal levels, standard digital CMOS technology. Power dissipation is 12 mW. The cell can be easily migrated in more advanced processes with area reduction. A migration in a 0.18-μm digital CMOS process has been achieved.